Long-Term Plasticity of Visually Evoked Potentials in Humans is Altered in Major Depression - Normann, Claus; Schmitz, Daniela; Fürmaier, Andrea; Döing, Carsten; Bach, Michael (Biological psychiatry (1969), 2007)
Long-term synaptic plasticity is a ubiquitous form of neuronal plasticity that regulates the strength of synaptic transmission in many brain areas. However, most data on long-term potentiation and long-term depression rely on research in animal brain slices. The role of synaptic plasticity in physiology and pathology of the functioning human brain remains obscure. Considering recent studies that provided evidence for a dysfunction of brain plasticity as the neurobiological basis of affective disorders, we assessed neural transmission and its plastic modulation in the visual pathway in healthy control subjects and patients with major depression. Recordings of visually evoked potentials (VEPs) in humans. Prolonged visual presentation of checkerboard reversals resulted in a sustained amplitude modulation of early components of subsequent VEPs. After a 10-min block of visual stimulation (two checkerboard reversals per second), the C1 component was reduced, whereas P1 and N1 were both significantly increased for >30 min. Chronic application of the selective serotonin reuptake inhibitor sertraline in healthy control subjects augmented these effects, whereas the polarity of the modulation was inverted in patients with severe major depression. Moreover, early VEP amplitudes were decreased in depressed patients when compared with matched control subjects and increased in normal control subjects after chronic intake of an antidepressant. Our results demonstrate that stimulus-induced response plasticity of VEPs can be induced in the human brain and is sharing properties with hebbian forms of synaptic plasticity. Major depression and antidepressant treatment of healthy control subjects differentially modulate amplitude and plasticity of evoked potentials. This study provides direct evidence in humans for a central role of synaptic plasticity in the pathophysiology of depression.